Draft genome sequence of Cellulomonas carbonis T26T and comparative analysis of six Cellulomonas genomes. Issue 1 (December 2015) - Zhuang, Weiping; Zhang, Shengzhe; Xia, Xian; Wang, Gejiao
Abstract MostCellulomonas strains are cellulolytic and this feature may be applied in straw degradation and bioremediation. In this study, Cellulomonas carbonis T26T, Cellulomonas bogoriensis DSM 16987T andCellulomonas cellasea 20108T were sequenced. Here we described the draft genomic information ofC. carbonis T26T and compared it to the relatedCellulomonas genomes. Strain T26T has a 3, 990, 666 bp genome size with a G + C content of 73.4 %, containing 3418 protein-coding genes and 59 RNA genes. The results showed good correlation between the genotypes and the physiological phenotypes. The information are useful for the better application of theCellulomonas strains.